New species of the genus Jacekaphorura (Collembola: Onychiuridae) from upper reaches of Kolyma river (North-East of Russia) - Babenko, Anatoly (Zootaxa, 2013)
Two new species of the genus Jacekaphorura from the North-East of Russia, viz. J. catherinae sp. nov. and J. furcata sp. nov., were described and illustrated. The former species clearly differs from the only previously known species of the genus by a high and variable number of dorsal pso, the latter can easily be distinguished due to specific structure of furcal remnant. The generic diagnosis and position within modern tribal subdivision of the Onychiurinae are discussed.